2013
DOI: 10.1017/jfm.2012.573
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds- and Mach-number effects in canonical shock–turbulence interaction

Abstract: The interaction between isotropic turbulence and a normal shock wave is investigated through a series of direct numerical simulations at different Reynolds numbers and mean and turbulent Mach numbers. The computed data are compared to experiments and linear theory, showing that the amplification of turbulence kinetic energy across a shock wave is described well using linearized dynamics. The post-shock anisotropy of the turbulence, however, is qualitatively different from that predicted by linear analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
144
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 27 publications
14
144
0
Order By: Relevance
“…72 Dittakavi and Chunekar 67 moreover found that the collapse of vapor structures causes a substantial increase in the baroclinic torque. In addition, turbulent fluctuations are amplified when processed by shock waves, see, e.g., Larsson et al 73 and Hickel et al 60 In a cavitating cloud collapse, this effect can be intensified by chain reactions of collapsing cavity arrays, as found by Lauer et al Figure 15 shows the wall-normal velocity fluctuations in y-and z-direction at the outlet extracted from our simulations. y = 0 and z = 0 correspond to the wall coordinate.…”
Section: -17supporting
confidence: 65%
“…72 Dittakavi and Chunekar 67 moreover found that the collapse of vapor structures causes a substantial increase in the baroclinic torque. In addition, turbulent fluctuations are amplified when processed by shock waves, see, e.g., Larsson et al 73 and Hickel et al 60 In a cavitating cloud collapse, this effect can be intensified by chain reactions of collapsing cavity arrays, as found by Lauer et al Figure 15 shows the wall-normal velocity fluctuations in y-and z-direction at the outlet extracted from our simulations. y = 0 and z = 0 correspond to the wall coordinate.…”
Section: -17supporting
confidence: 65%
“…6 And the vortices can be enhanced after they pass through the shocklets, e.g., see Ref. 21. However, the long filaments shown here usually locate right on shocklet surfaces in the compression region.…”
mentioning
confidence: 62%
“…13-17. Compressible turbulence has been studied extensively in past. This includes the shockturbulence interaction [18][19][20][21] and compressible isotropic turbulence, [22][23][24] to name a few. However, there are relatively fewer studies on compressible turbulence laden with inertial particles despite its importance in many phenomena.…”
mentioning
confidence: 99%
“…As aero-acoustic forcing in 188 N. Alferez and E. Touber turbomachinery is a significant source of premature turbine-blade fatigue, this result showed the importance of shock/turbulence interaction and how the linear interaction analysis (LIA) is relevant in studying it, the most recent version of which may be found in Wouchuk, Huete &Velikovich (2009) andLarsson (2016a,b). This relevance has grown recently with favourable comparisons against state-of-the-art numerical simulations of the fully nonlinear interaction (Larsson & Lele 2009;Donzis 2012;Sinha 2012;Larsson, Bermejo-Moreno & Lele 2013;Ryu & Livescu 2014;Quadros et al 2016a,b). Lee, Lele & Moin (1997), Larsson & Lele (2009), Larsson et al (2013) and Ryu & Livescu (2014) demonstrated the ability of LIA to accurately predict the post-shock turbulent kinetic energy, which opened the way for turbulence modelling based on LIA.…”
mentioning
confidence: 99%
“…This relevance has grown recently with favourable comparisons against state-of-the-art numerical simulations of the fully nonlinear interaction (Larsson & Lele 2009;Donzis 2012;Sinha 2012;Larsson, Bermejo-Moreno & Lele 2013;Ryu & Livescu 2014;Quadros et al 2016a,b). Lee, Lele & Moin (1997), Larsson & Lele (2009), Larsson et al (2013) and Ryu & Livescu (2014) demonstrated the ability of LIA to accurately predict the post-shock turbulent kinetic energy, which opened the way for turbulence modelling based on LIA. An exact analytical model of the interaction based on a closed form of several turbulent quantities extracted from the LIA was proposed by Wouchuk et al (2009).…”
mentioning
confidence: 99%